2021
DOI: 10.3390/nu13113758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inositol-Enhanced Bonded Arginine Silicate Ingestion on Cognitive and Executive Function in Gamers

Abstract: Inositol stabilized arginine silicate (ASI) ingestion has been reported to increase nitric oxide levels while inositol (I) has been reported to enhance neurotransmission. The current study examined whether acute ASI + I (Inositol-enhanced bonded arginine silicate) ingestion affects cognitive function in e-sport gamers. In a double blind, randomized, placebo controlled, and crossover trial, 26 healthy male (n = 18) and female (n = 8) experienced gamers (23 ± 5 years, 171 ± 11 cm, 71.1 ± 14 kg, 20.7 ± 3.5 kg/m2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The IBM ® Version 28 SPSS ® statistical package (IBM Corp., Armonk, NY, USA) was used to analyze data. Adequate sample size was determined based on an expected improvement of 5% with a power of 85% in primary outcome cognitive function related variables observed in our prior study [25,[41][42][43]. The n-size evaluated also had sufficient power to assess clinically significant side effects consistent with similarly designed studies conducted in our lab [41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IBM ® Version 28 SPSS ® statistical package (IBM Corp., Armonk, NY, USA) was used to analyze data. Adequate sample size was determined based on an expected improvement of 5% with a power of 85% in primary outcome cognitive function related variables observed in our prior study [25,[41][42][43]. The n-size evaluated also had sufficient power to assess clinically significant side effects consistent with similarly designed studies conducted in our lab [41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate sample size was determined based on an expected improvement of 5% with a power of 85% in primary outcome cognitive function related variables observed in our prior study [25,[41][42][43]. The n-size evaluated also had sufficient power to assess clinically significant side effects consistent with similarly designed studies conducted in our lab [41][42][43][44][45]. Participants were randomized to treatments using a balanced Latin Square designer program [46].…”
Section: Discussionmentioning
confidence: 99%
“…Trial duration, start speed, percentage of targets correctly identified, and the total score were evaluated to assess performance. We previously reported a test-retest Cv of identifying correct targets from this test of 6.5% [26].…”
Section: Light Tracking Reaction Testmentioning
confidence: 84%
“…sourceforge.net; accessed on 14 October 2021) [32]. A detailed description of each test and methods employed for the PEBL test in our lab was previously described [26,33]. The assessment battery included the Berg-Wisconsin Card Sorting Task test (BCST) which uses reaction time and accuracy of sorting cards to evaluate reasoning, learning, executive function, attention shifting (i.e., flexibility in responding to changing reinforcement schedules), and impulsiveness [32,[34][35][36][37]; the Go/No-Go Task test that assesses response control and sustained attention in responding ("Go") or not responding ("No-Go") to seeing the letters P or R appear on a computer monitor [34,35,38]; the Sternberg Task test (STT) that entails identifying visual stimuli as either present or absent within 2, 4, and 6 letter sequences in 3, 6, 9, 12, 15, or 18-second intervals to assess short-term/working memory involving cognitive control processes with the resulting reaction time and accuracy [34,35,39]; and the Psychomotor Vigilance Task test (PVTT) that examines general attention via sustained attention reaction times by reacting to a visual stimulus using a keyboard [32,34,35,40,41].…”
Section: Cognitive Assessmentmentioning
confidence: 99%
See 1 more Smart Citation